Internet of things with Python interact with the world and rapidly prototype IoT applications using Python - Hillar, Gastón C. (Packt Publishing, 2016)
Interact with the world and rapidly prototype IoT applications using Python About This Book Rapidly prototype even complex IoT applications with Python and put them to practical use Enhance your IoT skills with the most up-to-date applicability in the field of wearable tech, smart environments, and home automation Interact with hardware, sensors, and actuators and control your DIY IoT projects through Python Who This Book Is For The book is ideal for Python developers who want to explore the tools in the Python ecosystem in order to build their own IoT applications and work on IoT-related projects. It is also a very useful resource for developers with experience in other programming languages that want to easily prototype IoT applications with the Intel Galileo Gen 2 board. What You Will Learn Prototype and develop IoT solutions from scratch with Python as the programming language Develop IoT projects with Intel Galileo Gen 2 board along with Python Work with the different components included in the boards using Python and the MRAA library Interact with sensors, actuators, and shields Work with UART and local storage Interact with any electronic device that supports the I2C bus Allow mobile devices to interact with the board Work with real-time IoT and cloud services Understand Big Data and IoT analytics In Detail Internet of Things (IoT) is revolutionizing the way devices/things interact with each other. And when you have IoT with Python on your side, you'll be able to build interactive objects and design them. This book lets you stay at the forefront of cutting-edge research on IoT. We'll open up the possibilities using tools that enable you to interact with the world, such as Intel Galileo Gen 2, sensors, and other hardware. You will learn how to read, write, and convert digital values to generate analog output by programming Pulse Width Modulation (PWM) in Python. You will get familiar with the complex communication system included in the board, so you can interact with any shield, actuator, or sensor. Later on, you will not only see how to work with data received from the sensors, but also perform actions by sending them to a specific shield. You'll be able to connect your IoT device to the entire world, by integrating WiFi, Bluetooth, and Internet settings. With everything ready, you will see how to work in real time on your IoT device using the MQTT protocol in python. By the end of the book, you will be able to develop IoT prototypes w...
Includes index. - Online resource; title from cover (Safari, viewed June 8, 2016)
Keywords: Python (Computer program language); Internet of things; Machine-to-machine communications; Python (Langage de programmation); Internet des objets; Communication entre machines; COMPUTERS; Programming Languages; Python